Genetic diversity of GH1 and LEP genes in Argentine llama [Lama glama] populations - Daverio, Maria Silvana (2014)
Compared to other domestic species, little is known about variability of genes related to energetic metabolism and growth in camelids. Here, we have analyzed leptin (LEP) and growth hormone (GH1) genes and characterized their variability in three local llama (Lama glama) populations from the Argentine Northwest. Eleven novel SNPs and one indel were identified in the Lep gene. In total, eight haplotypes were found for LEP and seven for GH1. Although geographical origin clustering was not observed, SNP and haplotype frequencies varied significantly among populations. Based on variation of both loci, we detected significant genetic differentiation measured through Fst values. Network analysis of LEP gene supported the well-documented history of hybridization in camelids previously identified by mtDNA analysis.